(untitled) (Research, Society and Development, 2021)
The demands arising from the socio-environmental context serve as a stimulus for the innovation of products and processes by the civil construction industry. A growing possibility is the use of materials based on biopolymers, which are obtained by non-conventional transformation routes and are not derived from petroleum. In this scenario, the objective of the study was to identify the scientific production related to the biopolymers used in the construction industry through a bibliometric analysis for the period from 2010 to 2020. The data repository used was Scopus Elsevier, applying the filters according to the criteria of inclusion and exclusion. The results indicate that the publications are distributed in journals in the Engineering areas and also in those related to Environmental Sustainability and that the most cited authors, Ilhan Chang, Gye-Chun Cho and Jooyoung Im, were also the most productive and influential on the subject. The largest scientific contribution on the use of biopolymers in civil construction was given by the United States, followed by India and South Korea. It can be observed a significant increase in the number of publications from 2019, which demonstrates the importance that the community Since then, scientific research has given to the theme and also the distribution of publications among the different countries and research institutions, demonstrating the interest in this area in the various continents.